Revitalisasi Pendidikan Vokasi Berbasis Kebutuhan Industri 4.0: Implikasi Kebijakan Pendidikan di Daerah Sub-Urban - Riki Satia Muharam; Ufa Anita Afrilia; Sudarma Sudarma (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The Fourth Industrial Revolution has significantly transformed the structure of the labor market, demanding a workforce equipped with advanced technical and digital skills. Vocational education plays a strategic role in preparing human resources to meet these challenges. However, suburban areas in Indonesia still face various obstacles such as inadequate infrastructure, limited access to technology, and vocational curricula that are often misaligned with local industry needs. This study aims to evaluate the extent to which vocational education in suburban regions addresses the demands of Industry 4.0 and to formulate contextual and inclusive policy approaches. Using a qualitative methodology and literature review, this research finds that revitalizing vocational education in suburban areas requires curriculum reform aligned with local industry needs, enhanced teacher competencies, integration of digital learning technologies, and strengthened partnerships with industry. The study provides policy recommendations based on local needs, positioning vocational education as a driver of local economic development and a key contributor to preparing a future-ready workforce in the digital era.